2018
DOI: 10.1007/s00264-018-3967-y
|View full text |Cite
|
Sign up to set email alerts
|

Examination of intra-operative core temperature in joint arthroplasty: a single-institution prospective observational study

Abstract: In our series, peri-operative hypothermia remains common for patients undergoing arthroplasty. Female gender, low pre-operative temperature, knee arthroplasty, and neuraxial anesthesia were associated with hypothermia. Further preventative strategies and studies on interventions to reduce hypothermia are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…Hannan et al (4) retrospectively analyzed 2,294 OPCAB patients in New York in 2007 and found that postoperative respiratory complications in patients with perioperative hypothermia were associated with increased incidence of reoperating, prolonged hospital stay, and increased mortality. A similar conclusion was also reached by a prospective observational study this year: perioperative hypothermia associates with increased blood loss, delayed wound healing, increased surgical-related infection, and prolonged hospital stay (28). The study followed up the short-term prognosis of patients (Table 5).…”
Section: Discussionsupporting
confidence: 58%
“…Hannan et al (4) retrospectively analyzed 2,294 OPCAB patients in New York in 2007 and found that postoperative respiratory complications in patients with perioperative hypothermia were associated with increased incidence of reoperating, prolonged hospital stay, and increased mortality. A similar conclusion was also reached by a prospective observational study this year: perioperative hypothermia associates with increased blood loss, delayed wound healing, increased surgical-related infection, and prolonged hospital stay (28). The study followed up the short-term prognosis of patients (Table 5).…”
Section: Discussionsupporting
confidence: 58%
“…The incidence of hypothermia reported by previous studies varied widely from 11.2% to 43.9% [11][12][13], which may be caused by different warming methods, anesthesia procedure, and operating room environment. According to previous studies, female gender, lower BMI, knee arthroplasty, neuraxial anesthesia, lower preoperative temperature, lower operating room temperature, and longer operation time are the risk factors for hypothermia in TJA [11,13,16]. Therefore, measures improving the control of modifiable risk factors may be able to reduce the rate of hypothermia.…”
Section: Discussionmentioning
confidence: 99%
“…Of relevant factors, the most important is organ/tissue perfusion and oxygenation. Perioperative hypothermia induces poor tissue perfusion, and several strategies have been proposed to avoid it, including preoperative or intraoperative warming [164,165]. A benefit of perioperative hyperoxia in non-critically ill adults has not been demonstrated [166].…”
Section: Intraoperative Care For Tja Patientsmentioning
confidence: 99%